Development and evaluation of introgression lines with yield enhancing genes of the Indian mega-variety of rice, MTU1010 - Punniakotti, E.; Kousik, M. B. V. N.; Chaitra, K.; Harika, G.; Dilip Kumar, T.; Vivek, G.; Balachandran, S. M.; Rekha, G.; Aleena, D.; Anila, M.; Hajira, S. K.; Mastanbee, S. K.; et al. (EJPB, ISPB, CPBG - Tamil Nadu Agricultural University, 2023)
MTU 1010 is an early maturing and high-yielding mega rice variety widely grown in an area of 3 Mha. It is characterised by limited grain number and panicle branching. To improve the grain number in MTU 1010, an IRRI breeding line, IR121055-2-10-5 was utilized as donor to transfer yield-enhancing genes Gn1a and OsSPL14 (associated with increased grain number and better panicle branching, respectively) into MTU1010 by Marker-Assisted Backcross Breeding (MABB). At each backcross generation, foreground selection was carried out with Gn1a and OsSPL14- specific molecular markers, whilst background selection was done with a set of SSR markers polymorphic between the IR121055-2-10-5 and MTU1010. With the use of a gene-specific marker, homozygous BC2 F2 plants carrying the yield-enhancing gene were identified and advanced through pedigree-method of selection till BC2 F6 and best performing ten lines were selected and evaluated in replicated station trials for yield contributing traits, where grain number and brancing per panicle exhibited high significant and positive correlation with single plant yield. Three promising lines namely RP6353-5-8-13-24, RP6353-26-13-39-5 and RP6353-32-12-8-16 with higher grain number and yield than MTU1010 were identified and nominated for evaluation in Initial Varietal Trial-Aerobic (IVT-Aerobic) of All India Crop Improvement Programme on Rice (AICRP), of which RP6353-26-13-39-5 (IET28674), was promoted for further testing.